Acessibilidade em espaços universitários: um estudo do Campus do Pici - UFC em Fortaleza - Silveira, Plínio Renan Gonçalves da (2019)
With the sanction of Law No. 13.409 of December 28, 2016, which amends Law No. 12.711/2012 (known as the “Quota Law”) to establish reserve openings for persons with disabilities in secondary and post-secondary technical courses of federal educational institutions, a new scenario presents itself, resulting in a considerable increase of students with disabilities at the Federal University of Ceará – UFC. In this sense, the present research questions if the spaces of UFC would be prepared for the reception of these students. The study is part of the theme of spatial accessibility in university spaces, having for spatial setting the Pici University campus at UFC, located in Fortaleza, with the purpose of evaluating its infrastructure and its impact on the reception of students with disabilities. Based on documentary research and semi- structured interviews, it presents a history of interventions carried out at the University to improve accessibility. The field research is based on empirical and qualitative methodologies from three different perspectives: “Exploratory Walkthrough” (RHEINGANTZ et al, 2009) through observation of the campus, “Technical-Functional Evaluation” (ORNSTEIN, ROMERO 1992) based on the parameters established in NBR9050/2015, NBR16537/2016, Decree 5.296/ 2004, among others, and finally, “Accompanied Tour” (DISCHINGER, 2000) from the perception of students with disabilities. The analysis is conducted on two scales: a general characterization of campus accessibility and a deepening through the delimitation of a “pre-defined path” and “key buildings” considering the points with greatest flow of students with disabilities. From this analysis, the study presents the challenges to be overcome to ensure the reception of these students, the opportunities for future work, as well as some recommendations for renovation and construction of accessible campuses.